Patient Perspectives on Personalized Risk Communication Using Polygenic Risk Scores to Inform Colorectal Cancer Screening Decisions - Shauna R. Goldberg, MPH; Linda K. Ko, PhD; Li Hsu, PhD; Hang Yin, MS; Charles Kooperberg, PhD; Ulrike Peters, PhD, MPH; Andrea N. Burnett-Hartman, PhD, MPH (AJPM Focus)
Introduction: Colorectal cancer is increasingly diagnosed in people aged <50 years. New U.S. guidelines recommend screening initiation at age 45 years. Providing personalized risk for colorectal cancer using polygenic risk scores may be an opportunity to engage this younger population in colorectal cancer screening. There is limited research on patient understanding of polygenic risk scores results and use of polygenic risk scores to inform colorectal cancer screening decisions. Methods: From May 2022 to June 2023, 20 Kaiser Permanente Colorado members aged 46–51 years who had been offered colorectal cancer screening but had never completed it signed consent to provide a saliva sample for colorectal cancer polygenic risk score analysis. After receiving personalized polygenic risk scores for colorectal cancer, participants completed a semistructured interview regarding the understanding of their polygenic risk scores, perceived colorectal cancer risk, and intention to screen. Thematic analysis was conducted using Atlas.ti, Version 8. Results: Of the 19 participants who successfully completed polygenic risk score–related testing and a semistructured interview, 13 were female, 14 never smoked cigarettes, 6 were Hispanic, and 13 were non-Hispanic White. One participant had high risk for colorectal cancer on the basis of polygenic risk score results. Qualitative interviews showed participants’ understanding of their results, trust in polygenic risk scores, perception of risk for colorectal cancer, plans to complete colorectal cancer screening, intent to share polygenic risk scores with healthcare providers, and concerns about genetic results impacting health care. Conclusions: Qualitative analyses suggest that participants were interested in and understood their polygenic risk score results. Further study is needed to develop guidelines, effective calls to action, provider engagement, and health education materials on use of polygenic risk scores for health decision making.